2002
DOI: 10.1124/jpet.102.037143
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Permeation Characteristics of a Model Opioid Peptide, H-Tyr-d-Ala-Gly-Phe-d-Leu-OH (DADLE), and Its Cyclic Prodrugs across the Blood-Brain Barrier Using an In Situ Perfused Rat Brain Model

Abstract: The permeation characteristics of a model opioid peptide, HTyr-D-Ala-Gly-Phe-D-Leu-OH (DADLE), and its cyclic prodrugs [acyloxyalkoxy-based cyclic prodrug of DADLE (AOA-DADLE), coumarinic acid-based cyclic prodrug of DADLE (CA-DALE), and oxymethyl-modified coumarinic acid-based cyclic prodrug of DADLE (OMCA-DADLE)] across the blood-brain barrier (BBB) were determined using an in situ perfused rat brain model. The rat brains were perfused with Krebs-bicarbonate buffer containing test compounds in the absence or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 28 publications
(46 reference statements)
1
29
0
Order By: Relevance
“…[8] There are a number of options to potentially formulate around gastrointestinal efflux transporters, however current studies demonstrate very little success in bypassing these transporters in the BBB. [24,25] There is also arguably greater significance in delineating the factors that contribute to influx transport through these cells, particularly with respect to POT members, as they could potentially serve as targets for effective CNS delivery.…”
Section: Discussionmentioning
confidence: 99%
“…[8] There are a number of options to potentially formulate around gastrointestinal efflux transporters, however current studies demonstrate very little success in bypassing these transporters in the BBB. [24,25] There is also arguably greater significance in delineating the factors that contribute to influx transport through these cells, particularly with respect to POT members, as they could potentially serve as targets for effective CNS delivery.…”
Section: Discussionmentioning
confidence: 99%
“…indicates intravenous injection method, for compounds not likely to be strongly bound to serum proteins, and thought to be weak substrates for transporters. b This work. c Aoyagi et al 1988. d Fukui et al 1991. e Summerfield et al 2007 (please note that the original publication has an error in Table 1 in situ units: cm/min are correct, not cm/s - Summerfield S., private correspondence). f Gratton et al 1997. g Takasato et al .1984. h Liu et al 2004. i Obradovic et al 2007. j Dagenais et al 2004. k Murakami et al 2000. l Cisternino et al 2003. m Dagenais 2000. n Cisternino et al 2001. o Cisternino et al 2004. p Levin 1980. q Dagenais et al 2000. r Dagenais et al 2001. s Fernstermacher 1989. t Bickel et al 1996. u Youdim et al 2004. v Cisternino et al 2004. w Chen et al 2002. x Cisternino et al 2003. y Parepally et al 2006. z Tamai et al 2000. aa Murata et al 1999. bb Bihorel et al 2007. cc Pardridge et al 1990. dd Momma et al 1987. ee Smith et al 1986. ff Greig et al 1990. gg Bourasset et al 2003. hh Greig et al 1987. ii Wu et al . 1998.…”
Section: Figures and Tablesmentioning
confidence: 99%
“…Previous in vivo studies in rats showed high biliary clearance and low brain penetration of OMCA‐DADLE 18,19. Additionally, in vitro studies demonstrated that while the conversion of this prodrug to DADLE in the target organ brain was too slow, its conversion in plasma was too fast 19.…”
Section: Discussionmentioning
confidence: 97%
“…In an attempt to improve the oral bioavailability and BBB permeation of peptides and peptidomimetics, our laboratory has synthesized cyclic prodrugs of opioid peptides 13–16. Compared to the opioid peptides, these cyclic prodrugs exhibited improved stability to hydrolytic pathways of metabolism and better permeation across various cell membranes in the presence of inhibitors of efflux transporters 17,18. However, efflux transporters such as P‐gp and MRP2 adversely affected the cell membrane permeation of the cyclic prodrugs by producing net basolateral‐to‐apical flux.…”
Section: Introductionmentioning
confidence: 99%